PENGARUH CORPORATE GOVERNANCE TERHADAP CORPORATE SOCIAL RESPONSIBILITY DAN KINERJA PERUSAHAAN YANG MENDAPATKAN INDONESIA SUISTAINABILTY REPORTING AWARDS - KARTINA NATALYLOVA (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2013)
This research aims to identify the influence of Good Corporate Governance, represented by public ownership, institutional ownership, board of director size, audit committee, on corporate social responsibility and corporate financial performance, and also to observe the possible influence of corporate social responsibility on corporate financial performance. This research examines 17 companies which are listed in Indonesian stock exchange (ISX) and have issued an audited financial statement for 2006-2011. The statics method use to test the hypothesis is path analysis. The result suggests that good corporate governance not influences both disclosure of corporate social responsibility and corporate financial performance and that corporate social responsibility significantly not influences corporate financial performance. There is no strong evidence to support the type of industries as an influencing factor of corporate social responsibility. Furthermore, we found that the latter condition would also apply whenwe analyze the influence nomination and remuneration committee on corporate financial performance.